OPTIMASI PORTOFOLIO REKSA DANA INDEKS BERBASIS ENVIRONMENT, SOCIAL, DAN GOVERNANCE BERDASARKAN INDEKS IDX ESG LEADERS (IDXESGL) UNTUK PT XYZ - Rashad Salusra, Rayhan
XYZ is an investment management company that is looking into the trend of sustainable investing and the potential for portfolio optimization methodology development. XYZ aims to develop an ESG-themed index fund using the IDX ESG Leaders (IDXESGL) index. This research aims to produce the portfolio allocation that has considered regulatory constraints in index fund portfolios set by the Financial Service Authority (OJK) for index funds. This research will use multi-objective optimization and has developed a decision variable that represents if each stock is allocated in the portfolio to consider regulatory constraints. The solution allocated 26 out of 30 stocks and outperformed the IDXESGL index in terms of expected return and ESG risk. Analysis showed that the allocation is heavily dominated by the financial sector, allocation behavior is sensitive towards parameter weights, and literature discussion showed potential issues regarding the concept of sustainable investment in the form of the underlying motivation that drives the trend of sustainability-themed investments.